(untitled) (Czech Journal of International Relations, 2017)
Karine Tournier-Sol, Chris Gifford (eds.): The UK Challenge to Europeanization: The Persistence of British Euroscepticism. 1st Edition. Basingstoke: Palgrave Macmillan, 2015, 259 s., ISBN-10: 1137488158, ISBN-13: 978-1137488152.